2004
DOI: 10.1111/j.1745-7599.2004.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Attitudes and Practices of Texas Nurse Practitioners

Abstract: The growing number of NPs providing care to patients can significantly impact public health through consistent health promotion in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
5
17
0
1
Order By: Relevance
“…Nurse respondents reported that the content of their health promotion mainly focused on lifestyle risk factors. This was also found in other studies (Latter et al 1993, Sourtzi et al 1996, WHB 1999, Reeve et al 2004. The main strategies nurses reported using to promote health were similar to the traditional health education approach.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nurse respondents reported that the content of their health promotion mainly focused on lifestyle risk factors. This was also found in other studies (Latter et al 1993, Sourtzi et al 1996, WHB 1999, Reeve et al 2004. The main strategies nurses reported using to promote health were similar to the traditional health education approach.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies indicated that heavy workload (Gott & O'Brien 1990, Latter 1994, Evans 1998, Chan & Wong 2000, Doherty et al 2000 and low staffing levels (Hayes 1990, Mitchinson 1995, Doherty et al 2000 prevented nurses from developing their health promotion role. Other literature reported lack of time as a significant barrier (Treacy et al 1996, Thomson & Kohli 1997, Twinn & Diana 1997, Haddad & Umlauf 1998, Nagle et al 1999, Doherty et al 2000, Furber 2000, Sarna et al 2000, Flemming & Thompson 2002, Reeve et al 2004. Likewise, nurses in the current study reported lack of time and staff were barriers.…”
Section: Discussionsupporting
confidence: 53%
“…1993, Latter 1994, Smith et al. 1995, Brennan 1996, Caraher 1998, Robinson & Hill 1998, Whitehead 1999, 2000, Latter 2001, Whitehead 2003, Reeve et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A literature search with TRA as theoretical framework predicting APNs' or NPs' intention to perform a behavior has not been as researched. Reeve, Byrd, & Quill (2004) studied health promotion attitudes and practices in Texas Nurse Practitioners. They found that Texas NPs have positive attitudes toward health promotion and support its practice.…”
Section: Theory Relevancementioning
confidence: 99%
“…There is minimal literature regarding APNs' awareness and attitudes toward screening adolescents for CSEC. One study did examine Texas NPs attitude and practice toward health promotion, revealed that NPs held positive attitudes toward health promotion and practice, only 60% screened and encouraged their patients due to a lack of time (Reeve, Byrd & Quill, 2004). Edinburgh and Saewyc (2009) presented data on the Runaway Intervention Program (RIP) from 2003-2004 with the first 20 patients enrolled.…”
Section: Chase and Stathammentioning
confidence: 99%